2021
DOI: 10.3390/e23020190
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Controlling Bias for Some Bayesian Inferences and the Relation to Frequentist Criteria

Abstract: A common concern with Bayesian methodology in scientific contexts is that inferences can be heavily influenced by subjective biases. As presented here, there are two types of bias for some quantity of interest: bias against and bias in favor. Based upon the principle of evidence, it is shown how to measure and control these biases for both hypothesis assessment and estimation problems. Optimality results are established for the principle of evidence as the basis of the approach to these problems. A close relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…n * evidence 10 1 -0.047 against 10 100 0.019 in favour 10 500 0.037 in favour 50 50 0.005 in favour Also, the cut-off for determining evidence for or against occurs at 0 2 = [(1 + ) log(1 + )]/ → ∞ as →∞, which implies that the associated p-value → 0. This general conclusion is not overly reliant on the particular prior chosen, see [21], and suggests that smaller p-values are necessary to determine evidence against as increases, since increases with .…”
Section: Example 2 Jeffreys-lindley Paradoxmentioning
confidence: 82%
See 1 more Smart Citation
“…n * evidence 10 1 -0.047 against 10 100 0.019 in favour 10 500 0.037 in favour 50 50 0.005 in favour Also, the cut-off for determining evidence for or against occurs at 0 2 = [(1 + ) log(1 + )]/ → ∞ as →∞, which implies that the associated p-value → 0. This general conclusion is not overly reliant on the particular prior chosen, see [21], and suggests that smaller p-values are necessary to determine evidence against as increases, since increases with .…”
Section: Example 2 Jeffreys-lindley Paradoxmentioning
confidence: 82%
“…Various optimality properties, in terms of bias, are established in [21] for this approach to characterizing/measuring statistical evidence. A satisfying overall conclusion from this is that, if bias assessments are held as being essential, then there are complementary roles for frequentism and Bayes.…”
Section: Example 2 Jeffreys-lindley Paradoxmentioning
confidence: 99%
“…We also need to establish theoretical results for scenarios that go beyond those covered in Section 3, and more critically to cases where the likelihood itself is misspecified in consequential ways. A reviewer also reminded us to study the issue of assessing likelihood-prior combination that could lead to substantial bias, in the sense of creating regions of parameter space that are highly probable a priori; see Baskurt et al (2013); Evans and Guo (2019). Applications to high-dimensional and/or non-parametric problems are another important direction to explore, and the growing literature on the relationship between prior and posterior concentrations (see for example van der Pas et al (2014) and Strawn et al (2014) and references therein) may provide some theoretical insight on this exploration.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…There is also the issue of bias which is interpreted here as meaning that the ingredients to the analysis, namely, the data collection procedure together with the model and prior, can be chosen in such a fashion as to produce a foregone conclusion. That such bias is possible is illustrated in Evans (2015) and Evans and Guo (2021) where also a solution to this issue is developed.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in Evans and Guo (2021), the control of bias is equivalent to the a priori control of coverage probabilities. The control over the biases is effected by ensuring that an appropriate amount of data is collected as it can be shown that both biases converge to 0 as the amount of data increases.…”
Section: Introductionmentioning
confidence: 99%